Perlindungan Hukum Bagi Petani Terdaftar Penerima KUR Pada Kasus KUR TANI Fiktif Di Kabupaten Lombok Timur - Zahara, Annisa; Wardani, Nizia Kusuma (Commerce Law, 2024)
The distributor of Farmer's People's Business Credit (KUR TANI). This research uses a type of normative research with a statutory approach method (Statute Approach), conceptual approach (Conceptual Approach), and case approach method (Case Approach) to describe the problem. Based on the results of the research and discussion, it was concluded that the forms of legal protection for registered farmers who receive KUR are divided into 2 (two), namely preventive legal protection and repressive legal protection, and the provision of sanctions or legal responsibility can be in the form of administrative sanctions, civil sanctions, and criminal sanctions. The procedure that farmers can carry out if their data is misused is to resolve disputes through litigation. Keywords: Credit; Fictitious; Legal protection